2020
DOI: 10.3390/agronomy10121889
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis Effect on the Vegetative Development of Cotton Plants and the Biocontrol of Spodoptera frugiperda

Abstract: Bacillus thuringiensis (Bt) is used worldwide as a tool for controlling lepidopteran pests. Recent studies have demonstrated the possibility of its use as an endophytic organism, controlling insects and promoting plant growth. In this aspect, strains of Bt toxic to lepidopteran pests were inoculated both onto seeds and into cotton plants and were assessed for effectiveness in controlling Spodoptera frugiperda and its effect on promoting plant growth. It was observed that the results obtained from the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…in 7-day-old wheat seedlings for the Bt isolates B-6066 and B-5689. Although da Costa et al 64 reported no mortality of Spodoptera frugiperda fed in cotton plants regardless of the form of inoculation, in 11-day old cotton Bt colonized plantlets for four Bt isolates tested (S1450, S1905, S2122 and S2124). The Bt strain S2122 that showed the highest adhesion of the spore/crystal complex to the seed coats was selected for in vitro toxicity assays using leaves collected from 18-, 23-and 30-day old Bt colonized plantlets.…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/ ...mentioning
confidence: 91%
See 2 more Smart Citations
“…in 7-day-old wheat seedlings for the Bt isolates B-6066 and B-5689. Although da Costa et al 64 reported no mortality of Spodoptera frugiperda fed in cotton plants regardless of the form of inoculation, in 11-day old cotton Bt colonized plantlets for four Bt isolates tested (S1450, S1905, S2122 and S2124). The Bt strain S2122 that showed the highest adhesion of the spore/crystal complex to the seed coats was selected for in vitro toxicity assays using leaves collected from 18-, 23-and 30-day old Bt colonized plantlets.…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/ ...mentioning
confidence: 91%
“…in 7‐day‐old wheat seedlings for the Bt isolates B‐6066 and B‐5689. Although da Costa et al 64 . reported no mortality of Spodoptera frugiperda fed in cotton plants regardless of the form of inoculation, in 11‐day old cotton Bt colonized plantlets for four Bt isolates tested (S1450, S1905, S2122 and S2124).…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/r...mentioning
confidence: 92%
See 1 more Smart Citation
“…in 7-day-old wheat seedlings for the Bt isolates B-6066 and B-5689. Although da Costa et al, 2020 64 reported no mortality of S. frugiperda fed in cotton plants regardless of the form of inoculation, in 11-dat old cotton Bt colonized plantules for four Bt isolates tested (S1450, S1905, S2122 and S2124). The Bt strain showed the highest adhesion of the spore/crystal complex to the seed coats, so it was selected for toxicity in vitro assays of leaves collected at 18-, 23-and 30-day old Bt colonized plantules.…”
Section: Activity Against Insect Pests In Plants Colonized With Bt St...mentioning
confidence: 95%
“…Most of the information on the insecticidal activity of Bt has been obtained applying the Bt products or its invertebrate-active proteins (belonging to a range of structural classes 64 ) externally [1][2][3] or expressing the toxin genes in GMO crops. However, the toxicity of Bt acting as a endophyte/rhizospheric bacterium is not well characterized.…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/r...mentioning
confidence: 99%